Association of a Sweetened Beverage Tax With Purchases of Beverages and High-Sugar Foods at Independent Stores in Philadelphia - Bleich, Sara N. (JAMA Netw Open, 2021)
IMPORTANCE: The relationship between a sweetened beverage tax and changes in the prices and purchases of beverages and high-sugar food is understudied in the long term and in small independent food retail stores where sugar-sweetened beverages are among the most commonly purchased items. OBJECTIVE: To examine whether a 1.5 cent-per-fluid-ounce excise tax on sugar- and artificially sweetened beverages Philadelphia, Pennsylvania, was associated with sustained changes in beverage prices and purchases, as well as calories purchased from beverages and high-sugar foods, over 2 years at small independent stores. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study used a difference-in-differences approach to compare changes in beverage prices and purchases of beverages and high-sugar foods (candy, sweet snacks) at independent stores in Philadelphia and Baltimore, Maryland (a nontaxed control) before and 2 years after tax implementation, which occurred on January 1, 2017. Price comparisons were also made to independent stores in Philadelphia’s neighboring counties. MAIN OUTCOMES AND MEASURES: Changes in mean price (measured in cents per fluid ounce) of taxed and nontaxed beverages, mean fluid ounces purchased of taxed and nontaxed beverages, and mean total calories purchased from beverages and high-sugar foods. RESULTS: Compared with Baltimore independent stores, taxed beverage prices in Philadelphia increased 2.06 cents per fluid ounce (95% CI, 1.75 to 2.38 cents per fluid ounce; P < .001), with 137% of the tax passed through to prices 2 years after tax implementation, while nontaxed beverage prices had no statistically significant change. A total of 116 independent stores and 4738 customer purchases (1950 [41.2%] women; 4351 [91.8%] age 18 years or older; 1006 [21.2%] White customers, 3185 [67.2%] Black customers) at independent stores were assessed for price and purchase comparisons. Purchases of taxed beverages declined by 6.1 fl oz (95% CI, −9.9 to −2.4 fl oz; P < .001), corresponding to a 42% decline in Philadelphia compared with Baltimore; there were no significant changes in purchases of nontaxed beverages. Although there was no significant moderation by neighborhood income or customer education level, exploratory stratified analyses revealed that declines in taxed beverage purchases were larger among customers shopping in low-income neighborhoods (−7.1 fl oz; 95% CI, −13.0 to −1.1 fl oz; P = .001) and individuals with lower education levels (−6.9 fl oz; 95% CI, −12.5 to −1.3 fl oz; P = .001). CONCLUSIONS AND RELEVANCE: This cross-sectional study found that a tax on sweetened beverages was associated with increases in price and decreases in purchasing. Beverage excise taxes may be an effective policy to sustainably decrease purchases of sweetened drinks and calories from sugar in independent stores, with large reductions in lower-income areas and among customers with lower levels of education.